(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
In the last decade, information and communication technology has been the essence of our life. New electronic devices such as smartphones, tablets and computers, and offer different possibilities of accessing the internet anytime, anywhere. The computer is one of the innovative technologies that is used as a medium between the human-being and language teaching and learning which is called Computational Linguistics. Computational linguistics is a twofold field that combines principles of linguistics and computer science to develop computational models and algorithms for understanding, processing, and generating human language. The primary goal of computational linguistics is to enable computers to interact with human language meaningfully and efficiently. It also provides tools and frameworks that can help students better understand language patterns, grammar, syntax, and semantics. For instance, Natural Language Processing (NLP) tools can help in learning new languages, offering translation, grammar correction, and text-to-speech features.